“INFLUENCE OF BRAND IMAGE AND PRICE DISCOUNT TO PURCHASE DECISION SRIWIJAYA AIRLINE TICKET” - Suganda, Uce Karna; Rachmawati, Mariana; Gustirani, Indri; Lisdayanti, Annisa; Wijaya, Ni Putu Nurwita Pratami; Bestari, Dinda Kayani Putri; Munawar, Fansuri; Dalimunthe, Gallang Perdhana (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to determine how the influence of Brand Image and Price Discount to Purchasing Decisions Ticket SRIWIJAYA Airlines. The factors tested in this study are Brand Image and Price Discount as independent variables. While the SRIWIJAYA Airlines Ticket Purchase Decisions as a Dependent Varible. The research method used in this research is descriptive methods and verifikatif. The population in this study are consumers who have used SRIWIJAYA Airlines. The sampling technique used in this study is non-probability sampling using a purposive sampling technique, with a total sample of 125 people. While the analysis method used in this study is the anlysis of the correlation coefficient and the coefficient of determination. The result showed that the Brand Image variable partially significantly influenced the SRIWIJAYA Airline Ticket Purchase Decision, as well as the Price Discount variable that had a significant effect on the Purchase Decision SRIWIJAYA Airline Ticket. Then based on the result of the F test the result of the study showed that the Brand Image variable and Price Discount influenced the SRIWIJAYA Airline Ticket Purchasing Decision. The E square values obtained by 65% of SRIWIJAYA Airlines Ticket Purchase decisions can be explained by the variabel Brand Image and Price Discount. While the remaining 35% of Purchase Decision. SRIWIJAYA AirlinesTicket.